Pengembangan Wisata dan Pemberdayaan Lokal Wisata Danau Ranau - Komang Wardiasa; M. Said Hasibuan (Puslitbang Akademi Relawan TIK Indonesia, 2025)
Lake Ranau is the second largest lake on the island of Sumatra which is located on the border of South Sumatra Province and Lampung Province and has great potential as a nature-based tourist area. However, tourism development in this region still faces various problems, including limited accessibility, suboptimal supporting facilities, weak environmental management, and low levels of empowerment of local communities. This research aims to analyze the impact of tourism development on the socio-economic conditions of the communities around Lake Ranau and identify opportunities and challenges in an effort to realize sustainable tourism. The research method used is qualitative descriptive with data collection techniques through literature studies, document review from related agencies, and SWOT analysis. The results of the study show that the development of Lake Ranau tourism makes a positive contribution to increasing community income, creating business opportunities, and absorbing labor, especially in the micro, small, and medium enterprises (MSMEs), trade, and tourism services sectors. However, it is necessary to improve the quality of infrastructure, strengthen environmental management, and synergy between the government, the community, and business actors to support the development of Lake Ranau tourism optimally and sustainably.